Gender- and age-specific associations of childhood maltreatment with peripheral serum inflammatory cytokines in middle school students - Jin, Zhengge; Li, Shuqin; Li, Ruoyu; Song, Xianbing; Zhang, Shichen; Sun, Ying; Tao, Fangbiao; Wan, Yuhui (Frontiers in Immunology, 2023)
The impact of childhood maltreatment on multiple inflammatory cytokines among middle school students remains to be elucidated.This study aimed to examine the associations of different types of childhood maltreatment with inflammatory cytokines (interleukin-10, interleukin-1β, interleukin-6, interleukin-8, and tumor necrosis factor-α) in middle school students, and to explore the differences in these associations between boys and girls and between late (≥15 and＜20 years) and early (≥11 and <15 years) adolescence. A total of 1122 students were recruited from a boarding middle school. Each participant was asked to respond to a detailed questionnaire on childhood maltreatment, from whom one blood sample was drawn via venous blood. Results from linear regression analysis showed that (1) in the overall sample there was no association between childhood maltreatment and inflammatory cytokines; (2) emotional abuse was significantly correlated with IL-1β only in girls (B = -0.16; 95% CI, -0.28~-0.03; p = 0.06); (3) in late adolescence, emotional abuse, emotional neglect, and childhood maltreatment had marked link with IL-8 (B = 0.39; 95%CI, 0.16~0.63; p = 0.01; B =0.20; 95% CI, 0.04~0.37; p = 0.08; B = 0.50; 95% CI, 0.18~0.82; p = 0.01, respectively). These findings also strengthened an inference regarding the effects of childhood maltreatment on inflammation of students in late adolescence.